Analysing the Mental Imagery Training to Improve the Ability of Petanque Sport Shooting Game: Literature Review - Eka Abdurrahman; Nasuka; Sulaiman; Hermawan Pamot Raharjo; Heny Setyawati (OVS LLC, 2024)
Objective. The purpose of this study was to determine the role of biomechanical mental imagery training analysis in improving the ability of Petanque Sports Shooting Game. Materials and methods. This review study was performed following the PRISMA standards for systematic reviews and meta-analyses. The studies were required to have been published within the previous four years, from January 2020 to July 2023. (1) petanque shooting; (2) mental imagery analysis were the keywords used in the search process. To conduct the study, the database Scopus and SINTA (Science and Technology Index) were used. Results. The findings of the literature review yielded a final sample comprising 7 relevant articles. Specifically, 3 articles focused on imagery training for enhancing petanque shooting results, while 4 articles examined the effects of petanque shot improvement on the shooting game abilities of this sport. Conclusions. This study revealed that mental imagery exercise analysis significantly improved the performance of petanque athletes in the match phase, enhancing their performance, motivation, and concentration, making it a valuable method for achieving positive effects on physical and mental performance in petanque athletes.